STORING THE INFORMATION INTO LONG TERM MEMORY AND ITS IMPACTS ON LEARNING MATHEMATICS - Fitriati (Jurnal Visipena, 2013)
Memory obviously plays an important role in knowledge retention. In particular, when learning mathematics students claim that much of what is taught in classrooms is soon forgotten and learning mathematics is difficult or not interesting. Neuroscience, through its study on long term memory, has tried to identify why these phenomena occur. Then some possible solutions are suggested. Understanding the processes of memory storage including acquisition, consolidation, recoding, storing and retrieval helps teachers to efficiently plan for effective learning activities. Therefore, this paper outlines the potential implication of long term memory to mathematics learning as well as suggests some learning strategies that might solve students‟ and teachers‟ problem in learning mathematics.